Exploring the influence of obesity, fatty acids, and current treatment modalities on the immune-metabolic profiles of adipose tissue in oesophageal cancer - O'Connell, Fiona Martina (Trinity College Dublin. School of Medicine. Discipline of Surgery, 2023)
Oesophageal adenocarcinoma (OAC) is a poor prognosis cancer with limited response rates to current standard of care treatments including chemotherapy and chemoradiotherapy. OAC has one of the strongest associations with obesity, its anatomical location is surrounded by the visceral adipose depot has been postulated to intensify this association. Adipose tissue is a regulatory organ with many downstream functions that are not fully understood, including its response to chemotherapy and radiotherapy. To better elucidate the role of visceral adiposity in this disease state, a full metabolic profile combined with analysis of secreted pro-inflammatory cytokines, metabolites, and lipid profiles were assessed using human ex-vivo adipose tissue explants from obese and non-obese OAC patients. These data were correlated to extensive clinical data including obesity status, metabolic dysfunction, previous treatment exposure, and tumour regression grades. In this thesis, we identified that visceral fat from obese OAC patients had significantly elevated oxidative phosphorylation metabolism profiles, increased secretion of mediators of immune cell recruitment and Th17 immunity, in addition to altered secretions of glutamine associated metabolites. Adipose explants from patients with metabolic dysfunction also demonstrated increased oxidative phosphorylation metabolism, and increased secretion of pro-inflammatory associated mediators and triacylglycerides. Adipose explants generated from patients who had previously received neo-adjuvant chemotherapy showed elevated secretions of pro-inflammatory mediators and a decreased expression of triacylglycerides compared with patients who received no neo-adjuvant treatment or chemoradiotherapy regimen. For those patients who showed the poorest response to currently available treatments, their adipose tissue was associated with higher glycolytic metabolism compared to patients who had good treatment responses. Dietary fatty acids have been strongly linked with metabolic heath, particularly oleic acid (OA) and palmitic acid (PA) which are differentially expressed with increasing obesity, in the circulation and at an adipose tissue level. We assessed whether these fatty acids would differentially affect the adipose tissue of non-cancer and OAC patients with respect to metabolic and secreted profiles and the role of the adipose secretome on immune cell function. We observed that exogenous PA induced differential effects on adipose tissue metabolism, significantly decreasing metabolic profiles of adipose tissue of OAC patients, an effect that was not observed in non-cancer patients. PA treatment elicited an immunosuppressive effect on the adipose secretome, most apparent in OAC patients. PA treatment in the adipose secretome also led to the observation of paradoxical effects on DC maturation and M? polarisation between OAC and non-cancer patients. To further interrogate the action of these fatty acids on the adipose tissue, we assessed we examined the action of these fatty when used in combination with irradiation. We observed that the immunosuppressive effects induced by PA were augmented by increasing irradiation and increasing visceral adiposity within OAC patients. PA treatment induced differential responses in adipose tissue metabolism and secretome of non-obese and obese OAC patients, which were more pronounced following exposure to increasing radiation. Adipose tissue from obese patients displayed higher reliance on oxidative phosphorylation in the unirradiated and decreased reliance on glycolysis following high dose radiation compared with adipose tissue from non-obese patients. However, this diminished reliance on glycolysis in adipose tissue from obese patients was reinvigorated by OA treatment. Interestingly, macrophages cultured with the PA treated adipose secretome with and without increasing irradiation demonstrated conflicting polarisation responses depending on patient obesity status. In the unirradiated setting, the adipose secretome of non-obese patients treated with PA decreased expression of markers associated with M1 phenotypes and increased markers associated with M2 phenotypes. In contrast, PA treated adipose secretome of obese patients differentially effected expression of these markers, increasing M1 markers and decreasing M2 markers. However, following exposure to the PA treated adipose secretome exposed to increasing irradiation, opposing results were observed. Next, we explored the downstream effects this irradiated and fatty acid treated adipose secretome could have on cancer cell metabolism and invasive capacity, by utilising a OAC cancer cell line FLO-1 and matched liver derived metastatic cell line FLO-LM. We identified that these cells employ different metabolic mechanisms with FLO-1 cells being more reliant on glycolysis, while metastatic FLO-LM cells utilise oxidative phosphorylation associated mechanisms as well as being acutely affected by inhibition of fatty acid oxidation. Further to this, we observed elevated secreted levels of sCD147, a factor known to drive metastasis, in the PA treated adipose secretome exposed to increasing radiation, which was most apparent in the obese adipose secretome. Inhibition of fatty acid oxidation, a mechanism known to support metastasis, was seen to have differential response in enhancing invasion of primary and metastatic towards the PA enriched adipose secretome, an effect that was further amplified by patient obesity status and increasing radiation treatment. The role of adipose tissue and the influence of obesity on cancer treatment response has been contentiously reported. We examined the influence chemotherapy and chemoradiotherapy regimens on adipose tissue metabolism and its secretome. We observed that chemotherapy and chemoradiotherapy differentially alter adipose tissue metabolism and secreted factors, with chemoradiotherapy significantly increasing pro-inflammatory associated mediators. Exogenous fatty acids differentially altered the adipose secretome in response to these treatments. However, both treatments combined with exogenous fatty acids showed significant increases in mediators of Th17 immune responses. The chemotherapy treated adipose secretome enhanced mitochondrial dysfunction in cancer cells, increasing their reliance on glycolysis. Whilst the chemotherapy treated adipose secretome significantly increased dendritic cell maturation markers, it also promoted anti-inflammatory macrophage phenotypes. The chemoradiotherapy treated adipose secretome in combination with fatty acids induced opposing effects on macrophage polarisation. In combination with OA, it decreased M1 primed expression of pro-inflammatory markers, whilst in combination with PA, it decreased M2 primed expression of anti-inflammatory markers. Overall, the body of research in this thesis has elucidated that adipose tissue has the potential to act as an influential mediator of cancer progression and treatment resistance. The adipose secretome is enriched with a series of factors that impact inflammatory and immune responses which are heavily influenced by patient?s demographics. Further to this, addition of external stresses such as exogenous fatty acids, increasing radiation or cytotoxic drugs can differentially affect the adipose secretome and its complex microenvironment, priming it to repress anti-tumour immunity and conferring cancer cells with enhanced metabolic and invasive capacity. Most significantly, this thesis identifies that obesity is a fundamental cause of the aberrant adipose tissue biology seen in these OAC patients. The obese adipose secretome contributes to a wider tumour microenvironment primed to support cancer progression and the establishment of metastasis highlighting the critical need to further address the cancer-obesity link and if this can be exploited to improve treatment responses and overall patient outcome.
APPROVED
Keywords: Oesophageal Cancer; Obesity; Fatty acids; Treatment response